A new species of Quinquelaophonte (Copepoda: Harpacticoida) from Argentina - Michel Sciberras; Verónica Natalia Bulnes; Néstor J. Cazzaniga (Zoologia (Curitiba), 2014)
Quinquelaophonte aestuarii sp. nov. (Copepoda, Harpacticoida) from Bahía Blanca estuary is the first record of Quinquelaophonte Wells, Hicks & Coull, 1982 in Argentina and its southernmost location in the world. The setal formula (P2: exopod 1.2.3-endopod 1.2.0; P3: exopod 1.2.3-endopod 2.2.1; P4: exopod 1.2.3-endopod 1.2.0) of the last segment of P2-P4, in both the exopod and the endopod, distinguishes this species from all known species in Quinquelaophonte, except for Quinquelaophonte varians Bjornberg, 2010. The new species differs from the latter in the setal formula of the antennule, the mouth parts and maxillipeds, the absence of an inner seta on the second exopod segment of P2, the length of the second exopod segment of P4 and in the shape of baseoendopod setae of P5.